2018
DOI: 10.1002/aic.16344
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐organic gels of simple chemicals and their high efficacy in removing arsenic(V) in water

Abstract: Metal‐organic gels (MOGs) have emerged as a class of functional materials that show great potential applications in the field of catalysis, energy storage, template synthesis, and environmental technology. The construction of functional MOGs and the control of functionality are still challenging due to complicated chemicals or routes involved in previous works. Here we report a series of tunable multifunctional MOGs by directly gelating between Fe3+ and simple chemicals, propanedioic acid (H2PA), succinic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…At the beginning of the stress sweep, G ′ was higher than that of G ″ under stress ranging from 1 to 400 Pa, which indicated that the elastic component was dominant in the system (Figure a). , The sol-to-gel transition point was defined as the intersection of the G ′ curve and G ″ curve at ∼400 Pa, indicative of the onset of damage of the hydrogel network . Subsequently, the time sweep showed that the damaged hydrogel could recover its initial G ′ and G ″ values within 30 s. Furthermore, the apparent viscosity (η) decreased significantly with increasing shear rates (Figure b), which demonstrated the shear thinning behavior of the gels, thus demonstrating the potential application of the hydrogels in in vivo injection …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…At the beginning of the stress sweep, G ′ was higher than that of G ″ under stress ranging from 1 to 400 Pa, which indicated that the elastic component was dominant in the system (Figure a). , The sol-to-gel transition point was defined as the intersection of the G ′ curve and G ″ curve at ∼400 Pa, indicative of the onset of damage of the hydrogel network . Subsequently, the time sweep showed that the damaged hydrogel could recover its initial G ′ and G ″ values within 30 s. Furthermore, the apparent viscosity (η) decreased significantly with increasing shear rates (Figure b), which demonstrated the shear thinning behavior of the gels, thus demonstrating the potential application of the hydrogels in in vivo injection …”
Section: Resultsmentioning
confidence: 88%
“…38,48 The sol-to-gel transition point was defined as the intersection of the G′ curve and G″ curve at ∼400 Pa, indicative of the onset of damage of the hydrogel network. 44 Subsequently, the time sweep showed that the damaged hydrogel could recover its initial G′ and G″ values within 30 s. Furthermore, the apparent viscosity (η) decreased significantly with increasing shear rates (Figure 5b), which demonstrated the shear thinning behavior of the gels, 50 thus demonstrating the potential application of the hydrogels in in vivo injection. 48 In addition, dynamic oscillatory rheometry was used to determine the recovery rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 MOA(Fe) showed high efficacy in removal of arsenic in water. 14 Therefore, it will be a good possibility to apply MOAs and their composites hybrided with CdS as efficient photocatalysts which has not been reported as far as we know.…”
mentioning
confidence: 98%